Outcomes of Myringoplasty In Underlay Technique - Razzak, Md Abdur; Murshed, KM Mamun; Sobhan, AKMA; Harun, Md Abdullah Al; Imtiaz, SM Nafeez (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Myringoplasty is one of the surgical techniques for the management of chronic suppurative otitis media with permanent perforation of tympanic membrane. It is defined as simple surgical repair of tympanic membrane perforation without doing ossicular reconstruction. Objective: To determine the success rate of myringoplasty and to examine whether the hearing improvement is a potential indication for surgery. Materials and Methods: This study was conducted in the Department of Otorhinolaryngology and Head and Neck Surgery, Shaheed Suhrawardy Medical College Hospital from January 2017 to December 2017 and 100 patients who underwent myringoplasty in this period were analyzed. A total of 100 patients with dry central tympanic membrane perforations of various sizes were included in this study. Results: Myringoplasty was performed in total of 100 patients. Male were (45%) and females were (55%). Twenty one (7%) of them belonged to age group of 10-20 years, 31 (31%) were in the age range of 21-33 years, 38(38%) were the age range 31-40 years while 24 (24%) aged between 41-50 years with mean age of 26.32 ±S.D 9.59 years. Overall success rate of graft uptake was noted in 88 (88%) out of 100 cases. Conclusion: Myringoplasty is a safe surgical procedure in achieving intact tympanic membrane and to improve the hearing loss. Therefore, underlay technique being technically simple should be preferred, but the ultimate decision about the technique to be employed depends on the surgeons preference and the site of perforation. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 99-102